Challenges in the identification of new thermolabile psychoactive substances: The 25I-NBOH case. (July 2020) - Belchior de Andrade, Ana Flávia; Elie, Mathieu; Weck, Christian; Jardim Zacca, Jorge; de Souza, Mônica Paulo; Caldas, Luíza Nicolau Brandão; Gonzalez-Rodriguez, Jose
Highlights: Thermolabile NPS can generate artefacts in the traditional GC–MS analysis. When analysed by GC, 25I-NBOH fragments into 2C-I and an ortho-phenolic benzyl ether (o-PBE). No method adjustments can refrain 25I-NBOH thermo degradation on GC analysis. DSC and TGA analysis clarify 25I-NBOH's thermal instability. Derivatization can overcome 25I-NBOH degradation in the GC–MS. Abstract: The continuous emergence of NPS over the last years poses a series of novel challenges for forensic analysts. Most of those new compounds are synthesized with minimal chemical modifications to the structure of already known chemicals in order to avoid regulations. Some of these new compounds may undergo chemical changes during analysis leading to misidentification and detrimental legal consequences. GC–MS is one of the most widely used analytical techniques employed by forensic laboratories all over the world for drug analysis. Nevertheless, thermolabile NPS, such as 25I-NBOH can generate artefacts in the traditional GC–MS analysis. In this paper, we describe the fragmentation mechanism of the 25I-NBOH into a major peak corresponding to 2C-I and a minor one corresponding to the associated ortho-phenolic benzyl ether (o-PBE), which exact identity is directly linked with the solvent used for the analysis. Also, a series of method adjustments is displayed, encompassing variation on the injector temperature, split ratio and flow ratio, although with no success to prevent 25I-NBOH thermo degradation in the GC injector. Furthermore, differential scanning calorimetry and thermogravimetric analysis demonstrated that 25I-NBOH's thermal stability is due to a smaller temperature window between fusion and decomposition points. Finally, we perform derivatization experiments and demonstrate how to overcome 25I-NBOH degradation in the GC/MS analysis.